Exploring the impact of a training program for continuing education facilitators—an empirical journey - Torres Mata, Irma del Carmen; Miranda Becerra, Jose Noe; Vázquez-Villegas, Patricia (Frontiers in Education, 2025)
IntroductionThis study assesses an andragogical teaching model, INSPIRA, deployed in continuing education (CE) programs at a private university in Mexico. Workshops have been conducted to train CE facilitators (instructors) on this model, which was first implemented in 2016. This research aims to evaluate the effectiveness of these teaching model workshops and to identify areas for improvement based on facilitators’ perceptions, drawing on the theories of competency development and job satisfaction.MethodsA mixed-methods approach was utilized, incorporating historical data, surveys, and focus groups. Historical data were gathered from institutional records, including teaching evaluations for 536 facilitators conducted both before and after their training on the teaching model. From this group, 158 facilitators completed a researcher-developed survey assessing the impact of the training. Furthermore, two focus groups were held with 16 facilitators in total.ResultsThe results indicated a statistically significant enhancement in teaching evaluations following the training, with mean evaluation scores increasing by 0.82 points on a 10-point scale (p ≤ 0.001). More than 60% of facilitators reported improvements in teaching clarity, relevance, and practicality. Approximately 65% expressed that the topic became more applicable to their work, while only 30% observed increases in visibility, recognition, or income. Qualitative feedback indicated that facilitators appreciated the model’s clarity, structure, and focus, but suggested that workshops should be tailored to specific continuing education programs, supplemented with ongoing support, and regularly updated.DiscussionIn conclusion, the workshops effectively improved facilitators’ teaching competency. However, there is a need to enhance the components of job satisfaction. Significant increases in teaching evaluations are associated with facilitators’ improvements in structuring sessions, applying adult learning principles, and using technology, boosting their confidence and professional identity. However, these benefits didn’t always lead to recognition or income, requiring institutional support. Tailoring workshops to different modalities and providing certifications could further enhance implementation and facilitator engagement. The reliance on self-reported data and the study’s singular institutional context limit the applicability of its findings.